Assessing Incremental Coastal Inundation Under Sea Level Rise: A MIKE21-Based Analysis of Revetment and Mangrove Defence Performance at Pantai Punggur, Johor - Ibrahim, Ili Nadhirah; Mokhtar, Mardiha; Daud, Mohd Effendi; Hamid, Nor Baizura; Razali, Muhammad Rizal; Jefri Din, Mohammad Ikhmal Siddiq; Mohd Bukari, Saifullizan; Musa, Mohd Azlan; Mohd Zailani, Muhammad Farhan Aimran; Ariffin, Effi Helmy (Journal of Science and Technology, 2026)
Sea level rise (SLR) poses an escalating threat to low-lying coastal zones, particularly in sedimentary and intertidal environments such as the west coast of Johor, Malaysia. This study evaluates the incremental inundation response at Pantai Punggur, Johor, under projected SLR conditions for 2030, 2050, and 2100, using 2023 as the baseline. Eleven cross-shore transects representing two coastal defence settings, revetment-protected shores and mangrove-buffered zones, were analysed through hydrodynamic simulations conducted in MIKE21. Model inputs included high-resolution bathymetry and topography, ERA5 meteorological data, in-situ tidal and current measurements, and NAHRIM AR6-based SLR projections. Results show a progressive increase in inundation extent throughout the study period. During early-stage SLR (2023 – 2030), revetments demonstrated higher effectiveness in delaying inland water intrusion, with shorter inundation distances relative to most mangrove-fronted transects. However, beyond mid-century, the performance gap narrowed, and by 2100, revetment-protected transects recorded greater inundation distances (327%) than mangrove-buffered transects (189%), indicating a decline in structural effectiveness under prolonged sea-level pressure. In contrast, mangrove zones displayed more gradual and consistent inundation progression, reflecting adaptive buffering capacity influenced by vegetation health and continuity. The findings highlight that while revetments provide strong short-term flood protection, their effectiveness diminishes over long-term SLR scenarios, whereas mangrove ecosystems offer sustained, nature-based resilience. The study underscores the need for hybrid coastal protection strategies that integrate hard structures with mangrove conservation and restoration to strengthen long-term shoreline stability and climate adaptation in Pantai Punggur and similar vulnerable coastlines.